Re-slicing the pie of patronage the politics of the internal revenue allotment in the Philippines, 1991-2010 - Hutchcroft, Paul D. (The Philippine Review of Economics, 2012)
Of all the provisions of the 1991 Philippine Local Government Code, none has generated more contention than the internal revenue allotment (IRA)?through which 40 percent of national internal revenues are to be shared with local governments. The stated goal is to enable provinces, cities, municipalities, and barangays to assume the responsibilities devolved to them in the code. For all the celebrated talk of promoting local autonomy and instituting fiscal decentralization, however, the IRA is also very much a story about the enhanced access of local politicians to patronage resources. This analysis surveys the political dynamics of the IRA from its inception through the administrations of Fidel Ramos, Joseph Estrada, and Gloria Macapagal-Arroyo. Particular attention is given to three tensions as they have evolved over time: (a) between the national executive and local politicians, (b) between national legislators and local politicians, and (c) among and within categories of local politicians.